Ecotoxicology of Polymetallic Nodule Seabed Mining: The Effects of Cobalt and Nickel on Phytoplankton Growth and Pigment Concentration - Rimei Ou; Hao Huang; Xuebao He; Shuangshuang Lin; Danyun Ou; Weiwen Li; Jinli Qiu; Lei Wang (Toxics, 2023)
In order to improve the understanding of the environmental impacts of polymetallic nodule mining, ecotoxicological studies were conducted on the growth of model phytoplankton species Skeletonema costatum and Prorocentrum donghaiense using cobalt and nickel. This study evaluated various physiological and ecological indicators, such as cell proliferation, chlorophyll a, pigments, total protein, and antioxidant enzyme markers. The results show that the introduction of low amounts of cobalt or nickel increased the growth rate of phytoplankton. The phytoplankton benefited from low concentrations of cobalt and nickel stress. The increased protein levels and decreased activity of antioxidant enzymes considerably impacted physiological responses during the promotion of cell abundance. High concentrations of cobalt or nickel resulted in decreased light-absorbing pigments, increased photoprotective pigments, an inactive chlorophyll content, decreased total proteins, and maximal antioxidant enzyme activity in phytoplankton. Throughout the experiment, both the phytoplankton protein and enzyme activity declined with prolonged stress, and the cells underwent age-induced damage. Thus, seabed mining’s repercussions on phytoplankton could result in both short-term growth promotion and long-term damage. These consequences depend on the impurity concentrations infiltrating the water, their duration, and the organism’s physiological responses.